Valuation Reversed – When Valuators are Valuated: An Analysis of the Perception of and Reaction to Reviewers in Fine-Dining - Fabian Heinrich Müller (Copenhagen Business School (CBS), 2018)
Our society has seen a proliferation of valuation devices leading to the existence of multiple devices that valuate the same product or service. Studies of valuation devices have demonstrated wide-ranging implications for the objects they valuate as well as for the context, in which they are embedded. However, what remains opaque is the understanding of how these valuation devices themselves are valuated by actors in and around the devices. Aiming to enrich this understanding, this thesis gives an answer to the following research question: How are multiple valuation devices valuated by the actors in and around the devices in one particular context, in this thesis the Copenhagen fine-dining context and what are implications of this valuation? Theoretically, this thesis mobilizes the notion of valuation devices and is built on two theoretical pillars that originate out of economic sociology: valuation studies and studies of devices. Through delving into their common roots and reviewing previous studies, this thesis finds that both areas of research suggest the aspect of multiplicity and the aspect of the valuation of valuation devices as aspects needing in-depth exploration. I aim to shed light on these two theoretical gaps. In addition, the thesis elaborates on the effects of valuation devices, centering on performativity and reactivity, introducing the former and going deeper into the latter.
hdl:10398/9632
Keywords: 650